Ultra-sonography study of the equine duodenal dynamic in pre- and post-liquid ingest (Veterinary Science, 2017)
Ultrasonography allows evaluating lhe functional dynamics of the digestive process of the horse. The functional duodenal activity was evaluated in ten adult horses standardizing the window of exploration and the average evacuation time. A previous 7 and 5 hour of solid and liquid fasting was done. At time zero and after the ingestion of six litres of water, thc numbers of contractions were assessed at 10 seconds, and at 5 and 10 minutes. The results exhibits significant differences between all the measured times with respect to the fasting time.
Keywords: Ultrasonography; Abdomen; Duodenum